THE NAIL - VARIOUS PHYSIOLOGICAL AND PATHOLOGICAL ASPECTS - REVIEW - Olimpia Dumitriu Buzia; Elena Diana Nichifor; Carmen Tiutiucă; Marian Ilie; Anca Petronela Moșneagu; Sergiu Ciprian Focșăneanu (Romanian Society of Oral Rehabilitation, 2023)
Nail research in recent decades has concerned most pharmacologists and dermatologists, as it offers a much safer and more concentrated alternative to conventional oral therapy. The understanding of the microstructure and composition of the nail is far from complete. The main objective of this article is to review the microstructure, composition and main diseases of the nails.